Implementation of Punishment and Guidance of Narcotics Offenders in Correctional Institutions Narcotics Class II A Langkat - Thondi; Fitria Ramadhan Siregar; Robi Krisna (ASIAN PUBLISHER, 2023)
This study was conducted with the aim to determine the Implementation of Criminal and Guidance Wargabinaan Narcotics Crime in Correctional Institution Narcotics Class II A Langkat and to know the obstacles faced by correctional officers and solutions that have been done by correctional officers in coaching inmates in order to realize the correctional system. The method used in this research is juridical sociological to get real legal research by going directly to the object, primary data obtained directly from the source through interviews with correctional officers and prisoners concerned, and secondary data used as supporting data in this study. From the results of the research obtained by the Criminal Implementation and Development of Wargabinaan, namely: Development of Religious Awareness through learning the Koran, istigosah, hadrah, and worship practices, Development of Nation and State Awareness through ceremonial activities and apples, Intellectual Development through libraries and information media such as television, Development of Legal Awareness through legal counseling, Development of Integration with the Community through Conditional Release, Conditional Leave and Leave before release. The obstacles faced in the Development of Personality of Prisoners are: Lack of quantity of employees, inadequate facilities and infrastructure, excess capacity of prisoners and detainees,namely: Lack of quantity of employees, Inadequate facilities and infrastructure, Excess capacity of inmates and detainees, Lack of coaching time, Constraints from the prisoners themselves and Constraints from the Community